Ameliorative Role of Curcumin and Ascorbic Acid on Alterations in Marker Enzymes and Oxidative Stress in the Liver of Albino Rats Caused due to Heavy Metals in Water - Kaur, Ramandeep; Kaur, Navdeep (Journal of Soil Salinity and Water Quality, 2025)
The male albino rats were exposed to a combination of variable doses of arsenic, cadmium, and lead through drinking water, with or without pre-treatment with a combination of curcumin and ascorbic acid in variable doses for 90 days. The activity of liver marker enzymes, i.e., acid phosphatases, alkaline phosphatases, alanine aminotransferases, and aspartate aminotransferases in plasma was observed to be significantly high in heavy metals-treated rats. However, groups receiving curcumin and ascorbic acid showed non-significant variations in enzyme activities, with the most notable improvement observed in rats exposed to low doses of heavy metals and high doses of the antioxidants. The oxidative stress markers revealed that malondialdehyde levels were significantly increased in heavy metal-treated rats, while the activities of antioxidant enzymes, such as superoxide dismutase and catalase, were significantly decreased. The rats treated with a combination of low doses of heavy metals and high doses of curcumin and ascorbic acid exhibited non-significant variations in oxidative stress parameters compared to the control group. These findings suggest that the combination of curcumin and ascorbic acid provides protection up to some extent against liver alterations caused by a combination of heavy metals above permissible limits in drinking water.